The legality of the October 7th 2001 attacks on Afghanistan under international law - Ismail, Ahmed (AUC Knowledge Fountain, 2017)
The U.S. and U.K. attacks on the territory of Afghanistan on 7 October 2001 were not justified as a legal application of their inherent right to self-defense under international law. The attacks of 9/11 on the World Trade Center were not armed attacks by the State of Afghanistan; neither did the U.S. letter to the Security Council nor official documents and statements prove Taliban’s responsibility and effective control over al Qaeda’s terrorist operation on the U.S. soil. Even if the U.S. and U.K. invoked Article 51, considering 9/11 as armed attacks, the 7 October 2001 attacks on the territory of Afghanistan still did not satisfy customary law requirements of self-defense; necessity, proportionality, and immediacy. In addition, the U.S. and U.K. arguments for anticipatory use of force in the face of imminent threats by Afghanistan were not supported by evidence to the Council. Moreover, both governments did not receive Security Council authorization to use force in self-defense when they attacked Afghanistan.